7(-3x+7)=-(-3x+-73)

Simple and best practice solution for 7(-3x+7)=-(-3x+-73) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(-3x+7)=-(-3x+-73) equation:


Simplifying
7(-3x + 7) = -1(-3x + -73)

Reorder the terms:
7(7 + -3x) = -1(-3x + -73)
(7 * 7 + -3x * 7) = -1(-3x + -73)
(49 + -21x) = -1(-3x + -73)

Reorder the terms:
49 + -21x = -1(-73 + -3x)
49 + -21x = (-73 * -1 + -3x * -1)
49 + -21x = (73 + 3x)

Solving
49 + -21x = 73 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
49 + -21x + -3x = 73 + 3x + -3x

Combine like terms: -21x + -3x = -24x
49 + -24x = 73 + 3x + -3x

Combine like terms: 3x + -3x = 0
49 + -24x = 73 + 0
49 + -24x = 73

Add '-49' to each side of the equation.
49 + -49 + -24x = 73 + -49

Combine like terms: 49 + -49 = 0
0 + -24x = 73 + -49
-24x = 73 + -49

Combine like terms: 73 + -49 = 24
-24x = 24

Divide each side by '-24'.
x = -1

Simplifying
x = -1

See similar equations:

| 2x+43=34 | | M+14=3M-8 | | x^3+5x^2=6x | | m+7+4=-8 | | 5(x-7.2)=14.5 | | -(3x+2)=-19x+62 | | 25.748=2*3.14*r^2+2*3.14*r*3.1 | | 5a+10b=450 | | 453.6672=2*3.14*r^2+2*3.14*r*13 | | 5b+10a=450 | | -1-0.28v=2 | | 5*26=x | | -5+3(6-x)=1 | | 4x*3=99+x | | 20x=.6 | | 10a+5b=450 | | -2(6p-5)+2p=8p-8 | | 2(0,3x-1)-0,6=4+0,1x | | 8+10y=9y-6 | | -16t^2+57=0 | | 17x=6x-22 | | 138-4x=32x+22 | | 10.5=3b-12.5 | | 4x+2x+96-22=88+4x | | 6-3x-5x-1=10 | | 4(3x-44)=4(2x-10) | | 4x^4-17x^2+18=0 | | 5x*3+17=69+2x | | -2(3x-4)+12=8 | | -16t^2+7.85t+57=0 | | 4-x-2-x=x | | 5x^2+4xy-12y^2=0 |

Equations solver categories